he path of daggers - Jordan, Robert, e uthor (New York : Tor, 1998)
As Rand al'Thor struggles to unite the nations for the Last Battle, the Seanchan invasion spreads across the land, Egwene rises in power, and alliances shift in unexpected ways as the forces of the Shadow grow stronger.
Keywords: Fantasy fiction; Magic -- Fiction; Imaginary wars and battles -- Fiction